Studying obesity-associated changes in white blood cell count (WBCs) and in some WBC-derived inflammatory markers in type 2 diabetic Patients under treatment with metformin monotherapy - صارم, زينب (Latakia University Journal -Medical Sciences Series, 2024)
This study aimed to evaluate the changes in (WBCs) and some WBC-derived inflammatory markers in type 2 diabetic patients under treatment with metformin monotherapy. A total of 47 metformin-treated T2DM patients were enrolled in this study from Tishreen University Hospital, Lattakia, Syria for a period of 3 months and divided into three BMI-based groups. FBG level, WBCs count, percentages of neutrophils and lymphocytes were measured at two time points during the treatment with metformin. The neutrophil/lymphocyte ratio (NLR), the platelet/ lymphocyte ratio (PLR) and the systemic immune-inflammation index (SII) were calculated and compared. Because the mean duration of T2DM diagnosis and using metformin as monotherapy by the studied patients were 8 ± 4 months, the mean value of all measured variables were within the normal reference ranges. No statistically significant change in total WBCs (7.278±0.99vs7.237±1.04 103/mm3), neutrophil percent (58.03±5.85 vs58.619±5. 53%), lymphocyte percent (34.174±5.90 vs33.685±5.44%) and platelets counts (237.667±26.17 vs 239.482± 21.76 103/mm3), NLR (1.789±0.56vs1.796±0.46), PLR (99.327±21.19 vs 103.685±28.65) and SII (417.726±116.89 vs 430.058±114.7) were observed between the begin of the study and after 3 months. Although there was a significant decrease in WBCs count (6.32±0.66*103/mm3) (P =0.004) and a significant increase in PLR (118.73±33.48) (P =0.046) in the obese group compared with WBCs count (8.5±0.79*103/mm3) and PLR (83.04±5.8) in the normal weight group at the begin of the study, these differences were not significant after 3 months of continuous using of metformin. Metformin may prevent or delay the development and progression of cardiovascular diseases among patients with type 2 diabetes, by exerting anti-inflammatory effect and controlling the changes in some inflammatory indices like WBC- derived inflammatory markers, regardless of presence or absence of obesity.